Is Valproate Depressogenic in Patients Remitting from Acute Mania? Case Series - Vasudev, Kamini; Sharma, Priya (Case Reports in Psychiatry, 2015)
Valproate is an effective antimanic agent and is recommended as a first-line medication in the treatment of acute mania. Current evidence based guidelines recommend that valproate should be given as a loading dose as it produces a rapid antimanic and antipsychotic response with minimal side-effects. However, no clear guidelines are available on the appropriate dosing or serum levels of valproate in the continuation or maintenance phase of bipolar disorder. We present 4 clinical cases to hypothesize that the higher doses of valproate, such as those used in the treatment of acute mania, may cause a depressive switch. So consideration should be given to reducing the dose of valproate if a patient develops depressive symptoms following recovery from the manic episode, as a therapeutic strategy. The cases also indicate that relatively lower doses and serum levels of valproate are effective in the maintenance phase compared to those needed in the acute manic phase of bipolar disorder. This is the first set of case series that questions the depressogenic potential of valproate in patients remitting from an acute manic episode. It highlights that different doses and serum levels of valproate may be therapeutic in different phases of bipolar disorder.